ECO-PHYSIOLOGICAL BEHAVIOUR AND YIELD EVALUATION OF TION OF ONION UNDER AGRI-HORTI-SILVICULTURE SYSTEM - SANGWAN, A. K; DHILLON, W. S.; SINGH, N. P.; GILL, P. P. S. (The Bioscan, 2018)
In agri-horti-silviculture model involving fruit trees, poplar (Populus deltoids Bartr. Ex Marsh) as timber tree and onion were evaluated for yield and eco-physiological parameters. Mean weight of Kharif and rabi onion was found maximum (62.59 and 69.57g) when it was grown along with pear as a single crop and differed significantly when grown under all other intercropping system. Minimum weight (43.61 and 50.35 g) was recorded under pear + poplar intercropping system. Average weight 60.2 g, size 5.17 cm and yield 61.54 Q/acre of Rabi onion was found higher as compared to Kharif onion due to more availability of congenial temperature and higher photosynthetic rate 5.74 µmolm-2s-1for growths. Onion showed better performance under partial shade in yield and yield contributing parameters and decreased as canopy advanced in age. Net photosynthesis, stomatal conductance and transpiration in onion were higher in pear alone than in highly shaded area of pear + poplar intercropping system. Change in micro-climate and resultant effect on physiology, yield and economics of onion under canopy are presented in this paper. The transpiration (E) rate of onion was lowest under shade conditions irrespective of the crop used in the experiment leading to more water use efficiency in the shade conditions than in open.